Unraveling natural carbonate variability in Narragansett Bay, RI using multiple high temporal resolution pH time series - Baskind, Abigail; Ahumada, Georgia; Gomes, Kristofer; Stoffel, Heather; Gu, Shuai; Davies, Andrew J; Wang, Hongjie (Frontiers in Marine Science, 2025)
The increase in atmospheric carbon dioxide (CO2) over the last 200 years has largely been mitigated by the ocean’s function as a carbon sink. However, this continuous absorption of CO2 by seawater triggers ocean acidification (OA), a process in which water becomes more acidic and more depleted in carbonate ions that are essential for calcifiers. OA is well-studied in open ocean environments; however, understanding the unique manifestation of OA in coastal ecosystems presents myriad challenges due to considerable natural variability resulting from concurrent and sometimes opposing coastal processes—e.g. eutrophication, changing hydrological conditions, heterogeneous biological activity, and complex water mass mixing. Developing a mechanistic understanding of carbonate chemistry variability and its drivers across different time scales is a critical first step in identifying the anthropogenic OA signal against background variability and predicting future OA in coastal systems. This study analyzed high temporal resolution pH data collected during 2022 and 2023 from Narragansett Bay, RI—a mid-sized, urban estuary that since 2005 has undergone a 50% reduction in nitrogen loading—with weekly, discrete bottle samples to verify sensor data. Over a year’s worth of data revealed a distinct diurnal cycle of pH, with pH increasing during the day and decreasing during the night, with an average daily range between 0.05 and 0.1 pH units. Further, we observed a strong seasonal cycles with higher mean pH in winter (8.07 ± 0.15) and lower mean pH in summer (7.72 ± 0.07). By separating the drivers of pH variability into effects from temperature, salinity, water mass mixing, biological activity, and air-sea gas flux, we determined that biological production has the most significant influence on pH from daily to annual timescales and in episodic pH changes. To a lesser extent, the seasonal air-sea CO2 exchange and temperature cycle further modified pH on monthly to seasonal timescales. The dominant influence of biological activity in modulating pH has allowed Narragansett Bay’s nutrient reductions, which have been successful in increasing bottom water DO and pH conditions, to modestly reduce summertime surface pH through reduced primary production. This study offers an in-depth understanding of Narragansett Bay’s natural carbonate variability and highlights the sensitivity of an estuary to water management policy. These findings will benefit future OA prediction and will ultimately assist in making environmental management decisions in coastal estuaries with implications for multiple coastal stakeholders.